2008 58th Electronic Components and Technology Conference 2008
DOI: 10.1109/ectc.2008.4549944
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of stacked die using die-to-wafer integration for high yield and throughput

Abstract: We have developed a die-to-wafer integration technology for high yield and throughput for the formation of high bandwidth, high performance, and short-distance interconnections in three-dimensional (3D) stack applications. The results show that multiple 70-µm thick die can be successfully assembled in stacks on top of a wafer using a single bonding step, rather than by repeated sequential bonding steps. In this study, 1-die, 3-die, and 6-die stacks were assembled and the electrical resistance of link chains co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 9 publications
0
12
0
2
Order By: Relevance
“…In this study, we used the CALM process [6] to improve throughput for chip level integration. We fabricated chip stacks to evaluate alignment accuracy and thermal reliability characteristics of the CALM process.…”
Section: Chip Level 3d Integration 31 Addressing Throughputmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used the CALM process [6] to improve throughput for chip level integration. We fabricated chip stacks to evaluate alignment accuracy and thermal reliability characteristics of the CALM process.…”
Section: Chip Level 3d Integration 31 Addressing Throughputmentioning
confidence: 99%
“…Generally, one by one sequential die assembly is slower and more expensive than batch assembly process, however die pick and place of multiple die can aide productivity. The authors previously reported CALM, in which cavities were used as stacking templates for chips on a wafer [6]. CALM has good potential for effective, inexpensive, and high throughput 3D fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional integration circuit (3DIC) has become a very promising technology in the semiconductor industry, recently [1][2][3][4][5]. By introducing the structure of through silicon via (TSV) inside the die, vertically multiple-die stack would be practicable.…”
Section: Introductionmentioning
confidence: 99%
“…This technology provides advantages of short interconnections, simple routing, reduced stray capacitances, miniaturization, and compact packaging. Due to the rapid development of 3DIC packaging, high density and fine pitch micro bumps technology has become the important topic in microelectronics industry [1][2][3][4][5]. However, fine pitch flip chip bonding has many challenges and issues in terms of package assembly process and package reliability performance.…”
Section: Introductionmentioning
confidence: 99%